Masyarakat Digital dan Problematika Kesejahteraan: Analisis Isi Wacana - Rutiana Dwi Wahyunengseh; Tiyas Nur Haryani; Priyanto Susiloadi; Lukman Fahmi (Universitas Sebelas Maret, 2022)
Digital society is a necessity, not only requiring adjustments to aspects of physical infrastructure, but also social infrastructure. This article presents a digital discourse analysis of the study of 11 Research Groups at the Faculty of Social and Political Sciences in 2022. The method used is content analysis, to examine the “digital” discourse of 41 proposal titles, which won funding from the University Research and Community Service Institute. The results of the study found that digital concepts are compared with the terms online, internet, social media, applications, Big Data. The term digital is discussed in the context of: the pillars of digital lifestyle, digital citizenship, digital commerce, and digital connectivity. The obstacle to the development of digital society is the limited public literacy about digital utilities. The study of the pillars of digital identity and artificial intelligence contextualization from the social humanities aspect is still wide open for development. In the realm of community, it is still necessary to develop communication, information and education strategies for the use of digital device utilities for the welfare of an inclusive society. The development of a digital society will change the quality of conventional public service relationships. Suggestions for further research is to develop a risk assessment of digital community development from a social humanities perspective.